2022
DOI: 10.1186/s12985-022-01768-4
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and specific serological ELISA for the detection of SARS-CoV-2 infections

Abstract: Background The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has triggered the worldwide coronavirus disease 2019 (COVID-19) pandemic. Serological assays for the detection of SARS-CoV-2 infections are important to understand the immune response in patients and to obtain epidemiological data about the number of infected people, especially to identify asymptomatic persons not aware of a past infection. Methods We recombinantly produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Another advantage of using the N protein as an antigen is the possibility of differentiating infected and noninfected vaccinated persons producing anti-S-protein antibodies. Although our data are in accordance with reports in the literature, a limitation of our work was the use of a single antigen, not taking into account the possible variability that may exist in the protein production and purification procedure [34].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Another advantage of using the N protein as an antigen is the possibility of differentiating infected and noninfected vaccinated persons producing anti-S-protein antibodies. Although our data are in accordance with reports in the literature, a limitation of our work was the use of a single antigen, not taking into account the possible variability that may exist in the protein production and purification procedure [34].…”
Section: Discussionsupporting
confidence: 86%
“…Noteworthy, previous studies regarding immunologic responses against the coronavirus subfamily indicated that the IgG antibody response against the N protein was more prominent than against the S protein [ 32 , 33 ]. In addition, previous studies with SARS-CoV-1 demonstrate that the serum durability of antibodies against the N protein is greater than antibodies against the S protein, making its use attractive for tracking viral infections for longer periods [ 34 , 35 ]. Another advantage of using the N protein as an antigen is the possibility of differentiating infected and noninfected vaccinated persons producing anti-S-protein antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were purified by immobilized metal ion affinity chromatography (IMAC) using a HisTrap TM HP column (GE Healthcare, Chicago, IL, USA). The N protein was expressed as previously described [17].…”
Section: Recombinant Proteins Expressed In E Colimentioning
confidence: 99%
“…The cutoff value was determined by Receiver Operating Characteristics (ROC) analysis to obtain the best sensitivity and specificity based on a maximal Youden index using GraphPad Prism versions 9.0.2 or 5.01 (Graph Pad Software, La Jolla, CA, USA). N-protein ELISA was performed as previously described [17].…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
See 1 more Smart Citation